Dampak Penyalahgunaan Narkotika, Psikotropika Dan Zat Adiktif Lainnya (Napza) Terhadap Perilaku Seks Pranikah - Harbia, Harbia; Multazam, Andi; Asrina, Andi (Window of Health : Jurnal Kesehatan, 2018)
Drug abuse of Narcotics, Psychotropic subtances and other addictive (NAPZA) substances causes adverse effects in social function and organs of the body to cause death.drug abuse of Napza makes them not think long will the consequences of sexual intercourse so that the impact on premarital sex. This study aims to explore and analyze informants in depth about the impact of drug abuse of NAPZA types of methamphetamine, marijuana and pills (inex, tramadol and somadril) on premarital sexual behavior. This research used is qualitative research phenomenology approach with descriptive with primary data collection technique through indepth interview as many as 10 residents drug abuse of NAPZA types of methamphetamine, marijuana and pills (inex, tramadol and somadril) on premarital sexual behavior. The result showed that resident abuse of methamphetamine can improving sexual performance so durable and aggresive but will add to the sensation of pleasure when combined methamphetamine with piils (inex, tramadol and somadril) simultaneously. Residents of marijuana abusers created a sensation of happiness and supress sexual desire. Residents abusers of the piils (inex, tramadol and somadril) stimulated the brain to be more passionate, self confident including sexual behavior